(untitled) (Journal of the College of Basic Education, 2024)
This research aims to identify the effect of the Keys to Knowledge strategy among second-year intermediate students in chemistry and their positive thinking. The researcher derived the following null hypothesis: “There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who will study chemistry according to the Keys to Knowledge strategy and the average scores of the control group students who will study the same subject in the usual way on the thinking scale.” Positive").An experimental design with two experimental and control groups was chosen, and to achieve the goal of the research, a purposive sample consisting of (86) students was chosen and distributed among the two research groups. The number of students in the experimental group was (44) students and the number of students in the control group was (42) students.To achieve the goal of the research, the researcher prepared the research tool, the Positive Thinking Scale: It consists of (five) domains with (7) items for each domain. The apparent validity was extracted by presenting it to a group of arbitrators in education and methods of teaching science and psychology, and its discriminatory power and coefficient were calculated. The difficulty of each item of the scale was measured using appropriate statistical methods, and the reliability was extracted using the Cronbach’s alpha method and reached (0.90).After analyzing the results statistically using a t-test for two independent samples, the results resulted in the superiority of the experimental group that studied using the Knowledge Keys strategy over the control group that studied using the usual method in the positive thinking scale.In light of the research results, the researcher explained a number of recommendations and proposals that were mentioned in the fourth chapter